Organic food consumption in China: food safety concerns, perceptions, and purchase behavior under the moderating role of trust - Cao, Dayu; Xie, Qiang; Yao, Xiaoying; Zheng, Yan (Frontiers in Sustainable Food Systems, 2023)
In tandem with economic growth and enhanced individual income levels, the demand for superior food quality has seen a significant uptick, leading to increased consumer interest in organic food products. However, studies focused on organic food consumption reveal a strikingly low conversion rate of this interest into actual purchasing behavior, particularly in the context of China. It is, therefore, crucial to implement effective strategies to bridge this gap, thereby fostering the growth of China's organic food sector. This research introduces the theory of perceived values and innovation resistance into the stimulus-organism-response (SOR) theoretical model, exploring the interrelationships among various facets of food safety concerns, perceived values, perceived risks, and organic purchasing behavior. Furthermore, the moderating influence of trust in these relationships is taken into account. Employing structural equation modelling, data from 352 organic food consumers in China's premier cities were analyzed. Findings substantiated the significant interplay between perceived values and risks with food safety concerns. It was also observed that perceived values had a positive and significant impact on purchasing behavior, while perceived risks exerted a negative and significant influence. Importantly, the relationship between nutritional value and risk barrier with purchase behavior was found to be moderated by the level of trust. This study may help organic food producers, retailers, and policymakers bridge the consumers' intention-behavior gap.